Multi-Stage Optimization of LHTESS by utilization of Y-shaped Fin in a rectangular enclosure. (October 2022) - Wang, Yinwei; Abed, Azher M.; Kumar Singh, Pradeep; Tag-Eldin, Elsayed; Arsalanloo, Akbar
Abstract: Rectangular cavities are efficient tools for latent energy storage which have versatile applications in industry. A great effort has been dedicated to optimize energy storage and melting performance of PCMs in these systems. In this work, a Y-shaped fin has been adopted in a rectangular enclosure filled with Lauric acid as PCM and has been optimized in three distinct stages to find the optimum case. Different parameters have been adjusted to enhance the melting of PCM which include length of base of the fins, length of each of the branches of fins separately and the angle between two branches. The best case selected at each stage of optimization has been selected for further enhancement in the next stage. Enthalpy-porosity approach was used to simulate the melting process. It was concluded that case 3 at optimization stage 1 and case 6 in optimization stage 2 outperform other cases as they can better improve the natural convection generated in the enclosure. Also case 8 with angle of 120 ° has the best performance among all cases with 23.3% faster melting time in comparison with the base case.